2011
DOI: 10.1111/j.1365-2958.2011.07831.x
|View full text |Cite
|
Sign up to set email alerts
|

RbsB (NTHI_0632) mediates quorum signal uptake in nontypeable Haemophilus influenzae strain 86-028NP

Abstract: Summary Nontypeable Haemophilus influenzae (NTHI) is a respiratory commensal and opportunistic pathogen, which persists within biofilms on airway mucosal surfaces. For many species, biofilm formation is impacted by quorum signaling. Our prior work shows that production of autoinducer-2 (AI-2) promotes biofilm development and persistence for NTHI 86-028NP. NTHI 86-028NP encodes an ABC transporter annotated as a ribose transport system that includes a protein (RbsB) with similarity to the Escherichia coli LsrB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 56 publications
4
71
0
Order By: Relevance
“…AI-2 uptake may result from a currently unknown AI-2 receptor in the RA genome which, just like the LsrB homologues in Salmonella typhimurium and E. coli or LuxP in V. harveyi [22], are involved in AI-2 uptake [23,24]. Moreover, one new gene, rbsB, which was associated with AI-2 uptake, has been identified in Haemophilus influenzae [25]. Hence, we speculate that potential AI-2 receptors might exist in RA and play roles in AI-2 uptake.…”
Section: Discussionmentioning
confidence: 96%
“…AI-2 uptake may result from a currently unknown AI-2 receptor in the RA genome which, just like the LsrB homologues in Salmonella typhimurium and E. coli or LuxP in V. harveyi [22], are involved in AI-2 uptake [23,24]. Moreover, one new gene, rbsB, which was associated with AI-2 uptake, has been identified in Haemophilus influenzae [25]. Hence, we speculate that potential AI-2 receptors might exist in RA and play roles in AI-2 uptake.…”
Section: Discussionmentioning
confidence: 96%
“…NTHI can cause chronic otitis media infection in the chinchilla, during which bacteria persist within biofilms for weeks or even months (19,20). Therefore, we used the chinchilla infection model to assess the role(s) of pdgX and/or hktE in persistence of NTHI within the middle-ear chamber.…”
Section: Resultsmentioning
confidence: 99%
“…Soluble mediators, released by bacteria, modulate the composition of NTHI lipooligosaccharides that effects biofilm maturation and persistence in vivo (144). Swords and colleagues showed that RbsB participates as a quorum regulated protein required for uptake of and response to the signaling molecule AI-2 (145). The consequence of a tryptophanase driven increase in indole on biofilm inhibition may be diminished through increased transport of AI-2.…”
Section: Discussionmentioning
confidence: 99%